Eating Disorders: Reviews on Update in Diagnosis and Management (Journal of Rangpur Medical College, 2022)
Eating disorders are common and frequently missed behavioral disorders associated with significant physical, mental and social morbidity and mortality. Among psychiatric illness, mortality rate of anorexia nervosa and bulimia nervosa is about 10% and 1% at 10 years of diagnosis respectively. All clinicians should ask about eating habits (such as dieting, binge-eating, and weight control behaviors etc) and weight concerns in high risk groups, even when they have no concerns about eating or weight. The DSM-5 and ICD-11 list 6 distinct eating disorders: 1) Anorexia nervosa, 2) Bulimia nervosa, 3) Binge-eating disorder (BED), 4) Avoidant/restrictive food intake disorder (ARFID), 5) Rumination disorder and 6) Pica. Since the incidence of eating disordered patients in appears to be rising, it is a time demanding issue to deliver multidisciplinary treatment for them. As eating disorders frequently involve multi-system disorders such as gastrointestinal, neurological and endocrine, early screening and assessment of patients with eating disorders is essential. Treatments for eating disorders depend on its types and focus on behavioral change, targeting normalizes the weight and eating habits. Depending on the severity of malnutrition and associated medical conditions, eating disorders may be treated with patient education , cognitive behavioral therapy (CBT), family-based treatment (FBT), specialist supportive clinical management (SSCM) and Pharmacotherapy (TCAs, MAOIs, and SSRIs).J Rang Med Col. September 2022; Vol. 7, No. 2:63-68